Convergence rate of regime-switching trees - Leduc, Guillaume (2016)
Considering a general class of regime-switching geometric random walks and a broad class of piecewise twice differentiable payoff functions, we show that convergence of option prices occurs at a speed of order (-ᵝ), where β = 1∕2 when the payoff is discontinuous and β = 1 otherwise.